Eur. IT 819: A Parallel - Zeltchenko, Vsevolod (Hyperboreus, 2025)
During a tense exchange with Orestes, Euripides’ Iphigenia appears to suggest that a happy marriage should erase a young woman’s memory of the events preceding it. This unusual idea has puzzled three recent commentators on the tragedy, P. Kyriakou, L. P. E. Parker, and E. Kearns, who suggest that v. 819 is corrupt. The article draws attention to the fact that the same notion is implied in a papyrus fragment of Erinna (F 4, 28–30 Neri). This parallel enables Iphigenia’s response to be interpreted more accurately: if she had been destined for a happy marriage, she would have forgotten not her prenuptial bath, but the fact that the water for it was given to her by her mother.